Exploring Greek Manuscripts in the Library at Wellcome Collection in London - Bouras-Vallianatos, Petros (Taylor & Francis, 2020)
This book offers new insights into a largely understudied group of Greek texts preserved in selected manuscripts from the Library at Wellcome Collection, London. The content of these manuscripts ranges from medicine, including theories on diagnosis and treatment of disease, to astronomy, philosophy, and poetry. With texts dating from the ancient era to the Byzantine and Ottoman worlds, each manuscript provides its own unique story, opening a window onto different social and cultural milieus. All chapters are illustrated with black and white and colour figures, highlighting some of the most significant codices in the collection.